Kuasa Roh dalam Mitos-mitos Sangihe : Suatu Telaah Struktural Antopologis LEVI-STRAUSS - Rindorindo, Irene D. C (Kajian Linguistik, 2016)
Sangiang Taumatiti and Ompung myths depict the belief of Sangihé people in spirit’s power which cannot be comprehended with logical reasoning, so that men must fulfill some requirements in order to make relationship with that beyond human powers work. The belief has been passed on through the generations in Sangihé community. Structuralist paradigm is therefore used to analyze relation between the myths and another structures found in Sangihé community. Thus, myth can be functioned to study deep structure of the community. Key words: myth, spirit, deep structure